2008
DOI: 10.1093/annonc/mdn419
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undertreatment in cancer pain. A review of published literature

Abstract: Nearly one of two patients with cancer pain is undertreated. The percentage is high, but consists of a large variability of undertreatment across studies and settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
564
2
19

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 759 publications
(597 citation statements)
references
References 40 publications
12
564
2
19
Order By: Relevance
“…4,5 Opioid therapy is a necessary component of pain control at the end of life, but primary medical teams often shy away from it. 6 Te involvement of a palliative medicine specialist can change this. A 2013 study showed that after a palliative care consult, patients with previously undertreated pain were more likely to be on a long-acting opioid and receive combination therapy with lower-potency adjunct medication.…”
Section: Opioid Treatment In Palliative Medicine: Unmet Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Opioid therapy is a necessary component of pain control at the end of life, but primary medical teams often shy away from it. 6 Te involvement of a palliative medicine specialist can change this. A 2013 study showed that after a palliative care consult, patients with previously undertreated pain were more likely to be on a long-acting opioid and receive combination therapy with lower-potency adjunct medication.…”
Section: Opioid Treatment In Palliative Medicine: Unmet Needsmentioning
confidence: 99%
“…A review of undertreated pain showed that more than 40% of cancer and AIDS patients reported inadequate treatment for severe pain. 6 An update to that study showed that up to a third of patients with cancer still report undertreated severe pain, even with the involvement of palliative medicine specialists. 8 Palliative care physicians may also fnd themselves treating chronic pain with opioids.…”
Section: Opioid Treatment In Palliative Medicine: Unmet Needsmentioning
confidence: 99%
“…When individual human resource characteristics were considered separately, none significantly predicted outcome (Model 3-1). When human resource characteristics were 12.3AE3.6 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Abbreviations: ECOG, Eastern Cooperative Oncology Group; SD, standard deviation.…”
Section: Organizational and Patient Characteristicsmentioning
confidence: 99%
“…5 However, according to recent systematic review, there was large variability in the adequacy of pain control, and under-treatment and inadequate pain control are common. 6 Pain control is a key component of palliative care, which aims to improve the quality of life for patients with lifethreatening illnesses. Assessment of outcome indicators for pain control is especially important for quality assurance of palliative care centers.…”
Section: Introductionmentioning
confidence: 99%
“…9,[17][18][19] However, we have a limited understanding of the demographic, clinical, and health service factors that influence pain management, specifically opioid use, in persons with cancer at the end of life. The objectives of this study were to use a populationbased method to assess the use of opioid analgesics within the community among older persons with CRC in the six months before death and determine factors associated with the use of opioid analgesics in this population.…”
Section: Introductionmentioning
confidence: 99%